2003
DOI: 10.1017/s0033291703008638
|View full text |Cite
|
Sign up to set email alerts
|

Life events: effects and genesis

Abstract: It is more than 40 years since a burst of studies in the late 1960s started what has become a substantial corpus of work, establishing the role of life events in psychiatric disorders (Brown & Birley, 1968; Paykel et al. 1969). Findings depended on advances in methodology. First, came development of a life events questionnaire and a scaling of their stress magnitude (Holmes & Rahe, 1967); then, replacement by more reliable and valid interview methods and better ways of distinguishing major and minor ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…This finding is consistent with a rich body of research showing that life events, specifically those involving interpersonal loss, loss of self-esteem, or humiliation, are associated with a wide range of depressive symptoms (Birchwood et al, 2005;Paykel, 2003). Possibly, a stronger differentiation between hopelessness depression and "regular" depression would emerge in longitudinal studies examining interactions between a negative attribution style and illness-related stress in psychosis.…”
Section: Discussionsupporting
confidence: 84%
“…This finding is consistent with a rich body of research showing that life events, specifically those involving interpersonal loss, loss of self-esteem, or humiliation, are associated with a wide range of depressive symptoms (Birchwood et al, 2005;Paykel, 2003). Possibly, a stronger differentiation between hopelessness depression and "regular" depression would emerge in longitudinal studies examining interactions between a negative attribution style and illness-related stress in psychosis.…”
Section: Discussionsupporting
confidence: 84%
“…Other studies have demonstrated that although depressed patients report experiencing more life events, depression may actually predispose people to be exposed to further life events, e.g. miscommunication between depressed and non-depressed partners causing further marital conflict (Joiner, 2002;Paykel, 2003;Weissman & Markowitz, 2002). There may also be an element of recall bias, with depressed patients more likely to recall negative events than non-depressed counterparts (Lewinsohn & Gotlib, 1995;Monroe & Hadjiyannakis, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…has its origin in theoretical proximal causes in CHD patients, then it can be argued that patients are depressed independently of CHD disease severity. Some of the wellestablished theoretical causes of depression in the general population are stressful life events, reduced positive reinforcement, and distorted cognitions (Beck, 1991;Lewinsohn & Gotlib, 1995;Paykel, 2003). These proximal causes of depression have corresponding theories of causality and evidence-based interventions, respectively: interpersonal theory, behavioural theory and cognitive theory (Beck, 1991;Davidson, Rieckmann, & Lesperance, 2004;Kanter, Callaghan, Landes, Busch, & Brown, 2004;Lewinsohn & Gotlib, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of this disease remains to be elucidated but several biological mechanisms have been proposed to increase the risk for depression such as the vascular depression hypothesis (Krishnan et al, 1997), systemic low-grade inflammation (Valkanova et al, 2013), endothelial dysfunction (Cooper et al, 2011) and chronic dysregulations of the HPA axis (Belvederi Murri et al, 2014). In addition, psychosocial 'vulnerability' factors, such as stressful life events (Paykel, 2003), distorted cognition (Beck, 1991) and Type D (distressed) personality (Pedersen et al, 2006), could also contribute to depression.…”
mentioning
confidence: 99%